Thyroid profile and autoantibodies in Type 1 diabetes subjects: A perspective from Eastern India - Debmalya Sanyal; Anirban Majumder; Soumyabrata Roy Chaudhuri; Sudip Chatterjee (Indian Journal of Endocrinology and Metabolism, 2017)
Context: There has been a rise in the incidence of type 1 diabetes mellitus (T1DM) in India. The prevalence of thyroid autoantibodies and thyroid dysfunction is common in T1DM. Aims: The aim of this study is to determine the incidence of thyroid dysfunction and thyroid autoantibodies in T1DM subjects, without any history of thyroid disease, and the prevalence of glutamic acid decarboxylase (GAD) antibody, Islet antigen-2 antibody (IA2), thyroid peroxidase (TPO), and thyroglobulin autoantibodies (Tg-AB) in T1DM subjects. Settings and Design: This was a cross-sectional clinical-based study. Subjects and Methods: Fifty subjects (29 males, 31 females) with T1DM and without any history of thyroid dysfunction were included in the study. All subjects were tested for GAD antibody, IA2 antibody, TPO antibody, thyroglobulin antibody, free thyroxine, and thyroid-stimulating hormone. Statistical Analysis Used: A Chi-square/pooled Chi-square test was used to assess the trends in the prevalence of hypothyroidism. A two-tailed P< 0.05 was considered statistically significant. Results: The mean age of the subjects was 23.50 years. 9.8% of subjects were below the age of 12 years, 27.45% of subjects were of age 12–18 years, 37.25% of subjects were of age 19–30 years, and 25.49% of subjects were above 30 years. 78% were positive autoantibody for GAD, 30% for IA-2, 24% for TPO, and 16% were positive for Tg-AB. A total of 6.0% of T1DM subjects had evidence of clinical hypothyroidism, but the prevalence of subclinical hyperthyroidism (SCH) varied from 32% to 68.0% for we considered different definitions of SCH as advocated by different guidelines. All subjects with overt hypothyroidism had positive GAD and thyroid autoantibodies. One (2%) subject had clinical hyperthyroidism with strongly positive GAD, TPO, and Tg-AB. Conclusions: We found a high prevalence of GAD, IA2, TPO, and Tg-AB in our T1DM subjects. A substantial proportion of our subjects had undiagnosed thyroid dysfunction with a preponderance of subclinical hypothyroidism. All T1DM subjects with overt hypothyroidism or hyperthyroidism had positive GAD and thyroid autoantibodies. The high prevalence of undiagnosed thyroid dysfunction highlights the importance of regular thyroid screening in T1DM subjects.